REVISITING JUVENILE JUSTICE: A RESTORATIVE APPROACH TO HOMICIDE ACCOUNTABILITY IN INDONESIA - Harefa, Beniharmoni; Aura Islami, Diajeng Dhea Annisa; Supardi, Supardi (Universitas Syiah Kuala, 2024)
Criminal penalties can be imposed for infractions, including those committed by minors. However, the purpose of sanctions extends beyond punishment; they also aim to promote restoration. Given that children involved in homicide cannot be held to the same legal standards as adults, the law prioritizes their psychological development and growth. This article seeks to clarify the nature of criminal accountability for juvenile offenders and to explore the law enforcement process in cases of murder involving young individuals. This research utilizes a literature review methodology, drawing data from relevant publications, journals, and books. The findings suggest that adolescent homicide offenses can be effectively addressed through a restorative justice framework that prioritizes rehabilitation over retribution. A key component of restorative justice is the Family Group Conference, which involves the families of both the perpetrator and the victim in the juvenile's accountability process.